Knowledge without Epistemology - Feyerabend, Paul K. (Filozoficzne Aspekty Genezy, 2024)
The universality of scientific principles, theories, laws is never purely “objective”, it has a strong anthropological component. A theory of knowledge invoking transhistorical agencies is therefore not only dead — it was never alive; its so-called successes are nothing but an immense chimera. Scientific research knows no universal boundary conditions or standards whether of a conventional, aprioristic, or empirical kind but uses and invents rules according to circumstance without regarding the selection as a separate “epistemic” act and often without realising that an important choice is being made.